Fatty Acids and Membrane Lipidomics in Oncology: A Cross-Road of Nutritional, Signaling and Metabolic Pathways - Ferreri, Carla; Sansone, Anna; Ferreri, Rosaria; Amézaga, Javier; Tueros, Itziar (Metabolites, 2020)
Fatty acids are closely involved in lipid synthesis and metabolism in cancer. Their amount and composition are dependent on dietary supply and tumor microenviroment. Research in this subject highlighted the crucial event of membrane formation, which is regulated by the fatty acids’ molecular properties. The growing understanding of the pathways that create the fatty acid pool needed for cell replication is the result of lipidomics studies, also envisaging novel fatty acid biosynthesis and fatty acid-mediated signaling. Fatty acid-driven mechanisms and biological effects in cancer onset, growth and metastasis have been elucidated, recognizing the importance of polyunsaturated molecules and the balance between omega-6 and omega-3 families. Saturated and monounsaturated fatty acids are biomarkers in several types of cancer, and their characterization in cell membranes and exosomes is under development for diagnostic purposes. Desaturase enzymatic activity with unprecedented de novo polyunsaturated fatty acid (PUFA) synthesis is considered the recent breakthrough in this scenario. Together with the link between obesity and cancer, fatty acids open interesting perspectives for biomarker discovery and nutritional strategies to control cancer, also in combination with therapies. All these subjects are described using an integrated approach taking into account biochemical, biological and analytical aspects, delineating innovations in cancer prevention, diagnostics and treatments.